2021
DOI: 10.5653/cerm.2020.03853
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of curcumin on chromatin quality, sperm parameters, and apoptosis following testicular torsion-detorsion in mice

Abstract: Objective: The chief outcome of testicular torsion in clinical and experimental contexts is testicular ischemia. Curcumin, a compound with anti-inflammatory and antioxidant properties, has fascinated researchers and clinicians for its promise in the treatment of fertility diseases. Methods: Thirty-five fully grown male mice were randomly classified into five groups: control, sham, testicular torsion, treatment group 1 (testicular torsion+short-term curcumin), and treatment group 2 (testicular torsion+long-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Finally, all surgical conditions were restored to their anatomical position, and the walls of inguinal canal were sutured. 8 …”
Section: Methodsmentioning
confidence: 99%
“…Finally, all surgical conditions were restored to their anatomical position, and the walls of inguinal canal were sutured. 8 …”
Section: Methodsmentioning
confidence: 99%
“…One of these pharmacological effects is to prevent or repair chemical or physical harms to testis and spermatogonial. For instance, curcumin can repair the harmful effects of testicular ischemia and improve sperm chromatin quality in mice (13). Also, it has been shown that curcumin is one of the antioxidants that could be used potentially to inhibit the harmful effects of Benzo(a)pyrene on sperm parameters, though it is ineffective in preventing all abnormalities (14).…”
Section: Discussionmentioning
confidence: 99%
“…The testicles and spermatic cord were returned to their anatomical position, and the muscular and cutaneous walls of the inguinal region were sutured. A day after the TT induction, extract administration was conducted for 10 consecutive days at 10 a.m. (Shahedi et al., 2021).…”
Section: Methodsmentioning
confidence: 99%